An Overview of the Health Issues of the Elderly: A Cross Sectional Study - Anil, Archana; John, Nimmy N; B P, Jaya Soorya; Doddaya, H (Journal of Drug Delivery and Therapeutics, 2021)
Background: In the changing era of our community posing a challengeable situation to the senior support-needing population of the community, there is a need to know the different kinds of problems faced by the elderly. In the view of all these facts, this study was conducted to study the various health related problems among geriatrics. Objective: To study various health related problems in elderly population. Materials and methods: This cross-sectional study was carried out in May to August 2020 in Ernakulam district of Kerala, India. 150 elderly (aged above 60 years) were interviewed using a predesigned questionnaire. Results: In the present study, 45.33% were males and 54.67% were females. Among the total elderly, 27.33% were illiterate, 56.00% had received primary education, and 14.00% had received secondary education while only 2.67% had received education up to the graduate level. The common health problems elderly was decreased vision (35.33%), followed by arthritis (13.33%), hearing problems (12.00%), urinary problems (8.00%), diabetes(6.00%), weight loss (4.67%), dental problems (4.00%), Chronic obstructive pulmonary disease (3.33%), Hypertension (3.00%), asthma and anaemia with (2.67%) each, fatty liver and cancer with (2.00%) each and Ischemic heart disease (0.67%) . Conclusion: The study highlights the common health problems the elderly face. In this study, it was found that the most prevalent health problem among geriatrics was vision impairment followed by arthritis and hearing impairment. Keywords: Geriatrics; visual impairment; Health problems; Arthritis; Ageing.